Tidally induced variations in vertical and horizontal motion on Rutford Ice Stream, West Antarctica, inferred from remotely sensed observations. Issue 1 (13th January 2017) - Minchew, B. M.; Simons, M.; Riel, B.; Milillo, P.
Abstract: To better understand the influence of stress changes over floating ice shelves on grounded ice streams, we develop a Bayesian method for inferring time‐dependent 3‐D surface velocity fields from synthetic aperture radar (SAR) and optical remote sensing data. Our specific goal is to observe ocean tide‐induced variability in vertical ice shelf position and horizontal ice stream flow. Thus, we consider the special case where observed surface displacement at a given location can be defined by a 3‐D secular velocity vector, a family of 3‐D sinusoidal functions, and a correction to the digital elevation model used to process the SAR data. Using nearly 9 months of SAR data collected from multiple satellite viewing geometries with the COSMO‐SkyMed 4‐satellite constellation, we infer the spatiotemporal response of Rutford Ice Stream, West Antarctica, to ocean tidal forcing. Consistent with expected tidal uplift, inferred vertical motion over the ice shelf is dominated by semidiurnal and diurnal tidal constituents. Horizontal ice flow variability, on the other hand, occurs primarily at the fortnightly spring‐neap tidal period ( M sf ). We propose that periodic grounding of the ice shelf is the primary mechanism for translating vertical tidal motion into horizontal flow variability, causing ice flow to accelerate first and most strongly over the ice shelf. Flow variations then propagate through the grounded ice stream at a mean rate of ∼29 km/d and decay quasi‐linearly with distance over ∼85 km upstream of the grounding zone. Key Points: Remotely sensed data capture the spatiotemporal surface velocity response of an ice stream and ice shelf to forcing by ocean tides Velocities are modulated nearly 100 km upstream of the grounding zone at the spring‐neap tidal period Periodic grounding of the ice shelf causes local stress changes that can propagate far upstream due to weakened lateral shear margins